SISTEM PENUNJANG KEPUTUSAN KENAIKAN JABATAN PADA PT. MITRA INFOSARANA MENGGUNAKAN METODE PROFILE MATCHING - Hidayat, Rahmat; Merlina, Nita (Jurnal Pilar Nusa Mandiri, 2013)
Accordance with the rules set by PT. Infosarana partners in the process of promotion positions, it would require the criteria to determine who will be elected to fulfill the vacant position. In the process of determining the position required a decision support system. One method that can be used for the Decision Support System is using the Profile Matching. This research will be appointed a case of finding the best solution base on the competence of employees at PT. Infosarana Partner Profile matching method. This method was chosen because it is able to select the best candidates from a number of existing employees, in this case, meant that candidates eligible employees whose positions are available based on the criteria specified. Research carried out by finding the weights for each attribute, such examples are the intellectual capacity aspects, aspects of work attitudes, and behavioral aspects, then carried ranking process that will determine the optimal alternative, the best employees